1982
DOI: 10.7567/jjaps.21s2.63
|View full text |Cite
|
Sign up to set email alerts
|

Zn3P2/ITO Heterojunction Solar Cells

Abstract: Heterojunction solar cells of Zn3P2/ITO have been fabricated by rf sputter depositing ITO films onto Zn3P2 multiple crystal, and their electrical and photovoltaic properties are studied. Multiple crystal boules of Zn3P2, 12–16 mm in diameter and 3 cm long with grain size of 1–5 mm in diameter, and resistivity ρ of 40–105 Ω-cm have been formed by vapor phase transport. The ρ of as-grown Zn3P2 has been reduced significantly by Ag doping above 400°C. A V oc of 0.24–0.32 V and a J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…These results demonstrate that the tuning of the graphene–semiconductor junction allows boosting the performance of the solar cell by improving parameters like V oc . The 1.9% efficiency achieved in this work is comparable with thin-film Zn 3 P 2 devices based on p–n junction solar cells. Even though our efficiency falls short from the highest reported Zn 3 P 2 cell efficiency of 5.96% (Mg–Zn 3 P 2 Schottky cell), , the performance of our graphene–Zn 3 P 2 has significant room for improvement. Using a thicker Zn 3 P 2 layer to improve light absorption, as well as a transparent conductive oxide as a top gate would increase the power efficiency of the device.…”
supporting
confidence: 53%
“…These results demonstrate that the tuning of the graphene–semiconductor junction allows boosting the performance of the solar cell by improving parameters like V oc . The 1.9% efficiency achieved in this work is comparable with thin-film Zn 3 P 2 devices based on p–n junction solar cells. Even though our efficiency falls short from the highest reported Zn 3 P 2 cell efficiency of 5.96% (Mg–Zn 3 P 2 Schottky cell), , the performance of our graphene–Zn 3 P 2 has significant room for improvement. Using a thicker Zn 3 P 2 layer to improve light absorption, as well as a transparent conductive oxide as a top gate would increase the power efficiency of the device.…”
supporting
confidence: 53%
“…30 In principle, the precise flux control in MBE should also enable the controlled incorporation of extrinsic dopants such as Ag, Mg and In. 13,14,[33][34][35] Previously, in addition to thin films and bulk crystals, Zn 3 P 2 has been obtained in the form of randomly oriented nanowires, nanoribbons, and nanotrumpets. [36][37][38][39][40][41][42][43] In most of these studies, nanowires were produced through chemical vapour deposition (CVD) or by a thermochemical method relying on a quartz capsule containing the precursors being heated in a furnace.…”
Section: Introductionmentioning
confidence: 99%
“…MBE also provides a path for precise incorporation of extrinsic dopants, such as magnesium or silver. [19][20][21][22] Several substrates have been employed for the epitaxial growth of zinc phosphide thin lms. 12,14,17,23 For example, we previously showed that single-crystal zinc phosphide akes can nucleate and grow defect-free on graphene as the interactions are restricted to van der Waals.…”
mentioning
confidence: 99%